A Cross-sectional Study on Patients' Perspective Towards Dermatology Outpatient Services from a Tertiary Care Center in Nepal - Prajwal Pandey; Raju Shah; Swati Rani (Nepal Journal of Dermatology, Venereology & Leprology)
Introduction: Patient-centered care has received greater prominence in recent years, and it is paramount to assess the patient’s satisfaction to improve the quality of healthcare services. The present study is aimed at understanding the patients’ perspectives regarding dermatology outpatient services offered at a tertiary care center to determine the areas for improvement for better patient satisfaction.